(untitled) (Economics and region, 2025)
Amid the era of digital globalization, social networks have become one of the most powerful forces shaping contemporary social, political, and economic dynamics. Objectives of the article to examine the role of social networks as a driving force of societal transformation, identify their beneficial and adverse impacts, and outline optimal approaches to their governance. The research adopts an interdisciplinary methodology that integrates content analysis, comparative assessment of international regulatory frameworks, and statistical evaluation of empirical data. The results demonstrate that while social networks enhance the democratization of communication, support the growth of small and medium-sized enterprises, and promote cultural integration, they simultaneously exacerbate the risks of disinformation, political polarization, and privacy violations. The analysis highlights that the most effective regulatory strategies combine governmental oversight, platform self-regulation, and independent algorithmic auditing. The findings and recommendations of this study provide valuable insights for academics, policymakers, and industry practitioners seeking to design ethically sound and socially responsible approaches to managing digital communication ecosystems.